2010
DOI: 10.1177/1363460710384645
|View full text |Cite
|
Sign up to set email alerts
|

Whatever happened to non-monogamies? Critical reflections on recent research and theory

Abstract: How to cite: Barker, Meg and Langdridge, Darren (2010). Whatever happened to non-monogamies? Critical reflections on recent research and theory. Sexualities, 13(6) pp. 748-772.For guidance on citations see FAQs. Whatever happened to non-monogamies? Critical reflections on recent research and theory AbstractThe last decade has seen an explosion of interest in consensually non-monogamous relationships. This paper critically reviews current research and theory in this area, focusing particularly on polyamory, swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
168
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 224 publications
(179 citation statements)
references
References 57 publications
2
168
0
9
Order By: Relevance
“…or asexuality. In any of these cases it is encouraging to see them there, given that all three have tended to be excluded from understandings of human sexuality in the past (Barker & Langdridge, 2010). Similarly, with the combinations of three symbols, it is unclear whether they are intended to represent forms of bisexuality or forms of non-monogamous relationship.…”
Section: The Book and Its Covermentioning
confidence: 99%
“…or asexuality. In any of these cases it is encouraging to see them there, given that all three have tended to be excluded from understandings of human sexuality in the past (Barker & Langdridge, 2010). Similarly, with the combinations of three symbols, it is unclear whether they are intended to represent forms of bisexuality or forms of non-monogamous relationship.…”
Section: The Book and Its Covermentioning
confidence: 99%
“…The Fewer the Merrier (TFTM) reports four empirical studies that draw attention to "our society's obsession with romantic ideals of fidelity," a welcome intervention "in the context of recent debates about same-sex marriage." There has been an explosion of qualitative work on non-monogamies in the past decade (Barker & Langdridge, 2010), and the quantitative studies reported here triangulate a halo effect surrounding monogamous relationships and the stigmatization of consensual non-monogamous (CNM) relationships. In this commentary, I argue that the contribution to this paper is best measured is seen through a lens that makes same-sex relationships more central to the analysis.…”
mentioning
confidence: 54%
“…I propose that the British nation may now best be thought of as founded upon mononormativity rather than solely heteronormativity. Here, mononormativity refers to the 'ideological force of couple culture' (Budgeon, 2008: 302), the presumed desirability of coupledom, and discrimination against those whose intimate lives do not fit this conventional dyadic form (see Adeniji, 2001;Barker and Langdridge, 2010;Pieper and Bauer, 2005;Wilkinson, 2012). Adrienne Rich (1980) introduced the notion of 'compulsory heterosexuality' to describe the ways in which heterosexuality is enforced through societal pressures and economic incentives; this article examines how these now help to maintain not just heteronormativity but also mononormativity.…”
Section: Introductionmentioning
confidence: 99%